In Vitro Cytotoxicity of a Ti-35Nb-7Zr-5Ta Alloy Doped with Different Oxygen Contents - Goto Donato, Tatiani Ayako [UNESP]; Almeida, Luciano Henrique de [UNESP]; Arana-Chavez, Victor Elias; Grandini, Carlos Roberto [UNESP] (Mdpi Ag, 2014)
Cp-Ti is the most common material used for dental implants, but its elastic modulus is around five times higher than that of bone. Recently, promising alloys that add Nb, Ta, Zr and Mo to Ti have been developed. The mechanical properties of these alloys are directly related to its microstructure and the presence of interstitial elements, such as oxygen, carbon, nitrogen and hydrogen. In this study, the in vitro cytotoxicity of Ti-35Nb-7Zr-5Ta (TNZT) alloys was analyzed in the as-received condition and after being doped with several small quantities of oxygen on a cultured osteogenic cell. The cell's morphology was also examined by scanning electron microscopy (SEM). The TNZT alloy presented no cytotoxic effects on osteoblastic cells in the studied conditions.
Keywords: Ti-35Nb-7Zr-5Ta alloy; MC3T3-E1 cells; biocompatibility; cell culture